ANALYSIS OF SOLUBLE FIBRIN MONOMER AS DIAGNOSTIC MARKER FOR ACUTE MYOCARDIAL INFARCTION AND ITS CORRELATION WITH CARDIAC TROPONIN I - Maimun Zulhaidah Arthamin; Lydiana Parmadi; Dwi Priyadi Djatmiko; Elvin Richela Lawanto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
The diagnosis of non-ST-segment elevation myocardial infarction (NSTEMI) is required early and accurate to avoid missing diagnosis and improve the rule out of AMI patients. There is a relationship between AMI and the state of hypercoagulation and/or thrombosis process. sFM is a protrombotic marker that is found to be associated with early AMI incidence compared to cTnI that increases after mionecrosis. The aim of this study is to determine that sFM can be used as biomarker for AMI and the correlation between sFM and cTnI. A cross-sectional analytic observational study was conducted among 23 AMI patients and 27 healthy controls. AMI were established using clinical, ECG and laboratory findings. sFM levels were measured with Stago Compact Max analyzer. Statistical analysis was performed using the Spearman's correlation coefficient, ROC curve analysis, and 2x2 contingency table. A significant correlation were found between the sFM and the cTnI (r=0.422, p<0.05). With a sFM cut-off level of 2.56 µg/mL, AMI could be diagnosed with sensitivity and specificity of 82.6% and 40.7%, respectively (AUC=0.638). Discussion. sFM is a new biomarker for systemic thrombus events, both cardiac and non-cardiac. Conclusions and Suggestions. sFM can be considered as an parameter of AMI. Similar studies with cohort method involving large number may be needed in the future study.